IMPLEMENTASI SISTEM INFORMASI WISUDA STIE YPPI REMBANG BERBASIS WEB - Mahmudi, Ahmad Aviv (Program Studi Teknik Informatika Universitas PGRI Ronggolawe, 2021)
Information technology is currently developing into something that is easy, inexpensive, and speeds up information processing in every field. The world of education is one area that is affected by these technological developments. The graduate registration service process at STIE YPPI Rembang currently still uses manual services so that it is not effective and efficient. The purpose of this research is to produce an information system application that is expected to assist registration officers and assist study programs in managing and controlling prospective graduation participants. The system that will be created is a web-based Graduation Information system and MySQL as the database. The method used is SDLC (System Development Life Cycle) with a waterfall process so that it can be easier to develop. With the Graduation Information System, it is hoped that it will provide convenience for students/prospective graduates, academic staff, and study programs.